2016
DOI: 10.15420/aer.2016.17.2
|View full text |Cite
|
Sign up to set email alerts
|

Holter Monitoring and Loop Recorders: From Research to Clinical Practice

Abstract: Since the 1960s, Holter monitoring has been a cornerstone for diagnosing suspected arrhythmias in patients of all ages. 1 The most common monitoring systems allow the continuous registration of three or more leads for 24-48 hours; newer Holter monitors allow continuous electrocardiogram (ECG) registration for 2 weeks.1 Extending the time of ECG registration will increase the diagnostic yield of Holter monitoring, especially for those rhythm disturbances that are infrequent but recurrent.1,2 This need for a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(61 citation statements)
references
References 65 publications
0
61
0
Order By: Relevance
“…The rating of the FIT set by BioMonitor 2 implanters was good or acceptable in the vast majority of patients, with the implantation procedure lasting for a median of 6.1 min (first cut to last suture). The ICM miniaturization trend continues and allows safe, minimally invasive surgical procedures . Although the Reveal LINQ (weight 2.5 g, volume 1.2 cm 3 , and insertion opening 8 mm) is smaller than the BioMonitor 2, this is at the expense of reduced device longevity (nominal battery life expectancy for Reveal LINQ of 2.5‐3.0 years vs BioMonitor 2 4‐6 years) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rating of the FIT set by BioMonitor 2 implanters was good or acceptable in the vast majority of patients, with the implantation procedure lasting for a median of 6.1 min (first cut to last suture). The ICM miniaturization trend continues and allows safe, minimally invasive surgical procedures . Although the Reveal LINQ (weight 2.5 g, volume 1.2 cm 3 , and insertion opening 8 mm) is smaller than the BioMonitor 2, this is at the expense of reduced device longevity (nominal battery life expectancy for Reveal LINQ of 2.5‐3.0 years vs BioMonitor 2 4‐6 years) .…”
Section: Discussionmentioning
confidence: 99%
“…Capable of monitoring for a period of several years, ICMs can demonstrate correlation between symptoms and arrhythmia, guide medical therapy for atrial fibrillation (AF), and help risk stratification in structural heart disease . Remote monitoring has overcome the problem of limited ICM storage capacity (∼1 h of electrocardiogram [ECG]) and allows earlier detection of and response to clinically relevant arrhythmia . Further device miniaturization, extended automation and features, and more accurate detection algorithms could expand the field of application for ICMs…”
Section: Introductionmentioning
confidence: 99%
“…Possible explanations for this heterogeneity include the differences in the methodology of diagnosis of AF, surgical approach, and patient characteristics in each study. Second, there have been significant advances in cardiac monitoring technology and electrophysiology studies (EKG, signal‐averaged EKG, Holter monitor) . It is possible that AF has been detected and diagnosed more frequently in the later studies, which may be influencing the findings of incidence trends of AF following heart transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Given the LR is a subcutaneously implanted foreign body there is the potential for infectious and skin/soft tissue erosion. Recent studies have demonstrated rates of LR infection between 2% and 4% whereas one report of 65 patients observed a single device infection and one instance of localized cellulitis, with both patients requiring LR explant . In the Damiano study no infectious complications were reported; however, this study followed patients for only a 12‐month period .…”
Section: Discussionmentioning
confidence: 84%